Sistem Pendukung Keputusan Penentuan Prioritas Pemeliharaan Jalan Menggunakan Metode PROMETHEE II (Studi Kasus: Dinas Pekerjaan Umum Dan Penataan Ruang Kabupaten Ponorogo) - Mahardhika Hendra Bagaskara; Muhammad Tanzil Furqon; Sutrisno Sutrisno (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Road infrastructure has an important role in supporting the economic, social and cultural sectors. The government as the road operator must prioritize the maintenance of the road periodically in accordance with the minimum service standards set. The strategic target of Directorate General of Highways one of them is the stability of the road that reaches 70%. Due to the number of broken roads, the number of complaints from the public, and the limited budget, the government must have priority on which roads should receive maintenance. The selection of road segments implemented by Ponorogo District Office of PUPR can be done by applying PROMETHEE II method to consider several alternatives and get the best alternative ranking based on the aspect of steady road conditions, unsteady road conditions, LHR, access and inter-district liaison. The method of Promethee II performs calculations with several stages: weighting, multicriteria preference index calculation for 4 types of preference ie, usual, quasi, linear, and the level and calculation of leaving flow, entering flow, and netflow. Based on the test, the highest accuracy on the use of the usual and quasi type of preference is 55.56% and the lowest accuracy on the use of linear preferences type is 45.83%. The degree of accuracy in testing is influenced by the weights used for each of the criteria and the type of preferences used in the calculation process.